Projeto gráfico de mídia musical e divulgação para a banda curitibana “Fake" - Ruppel, Deborah Talita (2012)
This graduation degree essay presents the development and execution of a musical media project including the graphic elements of cover, label, artwork, and promotional material as flyers, posters, prints and e-commerce for the band “Fake” from Curitiba, Brazil. The project methodology was based on the realization of a briefing, followed by the analysis of the material that the band already had, analysis of similar material and the creation of a semantic panel. The imagery concept was taken from the analysis and the information obtained in the briefing, using the reference of the Mexican celebration “Dia de Los Muertos”. After the theoretical research, the constituent’s parts of a musical compact disk artwork, promotional material and some extra material as t-shirts, bottons between others were developed.